Potret Ashabul Ukhdud dalam Al-Qur’an (Kajian Kitab Shafwah At-Tafasir) - Aditya Rizki Ramadhan; Septiawadi Kari Mukmin; Muhammad Tauhid (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines Muhammad Ali Ash-Shabuni's interpretation of the story of Ashab al-Ukhdud in QS. Al-Buruj verses 4–11 as presented in his exegesis Shafwah at-Tafasir focusing on the meaning of "qutila ashab al-ukhdud", the identity of the perpetrators, the forms of cruelty and the attitude of believers in facing oppression. The method used is library research with a qualitative descriptive approach. The primary data sources include the Qur'an, Hadith and the book Shafwah at-Tafasir while secondary sources include classical exegesis literature and relevant journals. Data collection techniques employ documentation, while data analysis uses descriptive-analytical method, which involves describing Ash-Shabuni's interpretation and then analyzing it to obtain a deeper understanding. The results show that Ash-Shabuni interprets the phrase "qutila aṣḥāb al-ukhḍūd" as a prayer of curse and condemnation, not merely a declarative statement. The perpetrators are tyrannical rulers who dug large trenches filled with blazing fire to burn believers alive, while the only "fault" of the believers was their faith in Allah. In conclusion Ash-Shabuni's interpretation affirms that this story contains strong theological messages: the steadfastness of faith as a non-negotiable principle, the certainty of divine justice whereby perpetrators receive the torment of Hell while patient believers receive Paradise as al-fawzu al-kabīr (the great victory), and the function of the story as a warning to disbelievers as well as spiritual reinforcement for oppressed Muslims across time.